Test-retest reliability and concurrent validity of athletic performance combine tests in 6-15-year-old male athletes - Gillen, Z. M.; Miramonti, A. A.; McKay, B. D.; Leutzinger, T. J.; Cramer, J. T. (The Journal of Strength and Conditioning Research, 2018)
Athletic performance combine tests are used by high school, collegiate, and professional American football programs to evaluate performance; however, limited evidence is available on performance combine test results in youth athletes. The purposes of this study were to report test-retest reliability statistics and evaluate concurrent validity among combine performance tests in 6-15-year-old male athletes. Sixty-nine young male athletes (mean ± SD; age = 10.9 ± 2.1 years, height = 154.4 ± 13.6 cm, body mass = 46.8 ± 16.0 kg) were divided into 3 age groups: 6-9 years (n = 16), 10-11 years (n = 26), and 12-15 years (n = 27). Participants completed 2 attempts of the vertical jump (VJ), broad jump (BJ), pro-agility (PA), L-cone (LC) drill, and 10-, 20-, 40-yd dashes. The results indicated that the older age groups performed better on most performance assessments compared with the 6-9-year group (p = 0.05). The combine tests demonstrated consistently adequate reliability for all age groups, except for the 10-yd dash, which was deemed unreliable. Evidence of concurrent validity, and possible measurement redundancy were observed in the VJ vs. BJ, PA vs. LC, and 20 vs. 40 yd, but zero- and first-order partial correlations suggested that only the PA and LC were redundant, and the PA may be superior for this age group over the LC. Although the VJ and BJ provide independent performance information regarding lower-body power, questions regarding the redundancy of the 20 vs. 40 yd remain unanswered from a measurement perspective.